2019
DOI: 10.3847/1538-4357/ab0082
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Components of the Ultra-fast Outflow in the Quasar PDS 456 from Chandra/HETGS, NuSTAR, and XMM-Newton Observations

Abstract: We present the spectral analysis of Chandra/HETGS and NuSTAR observations of the quasar PDS 456 from 2015, and XMM-Newton and NuSTAR archival data from 2013-2014, together with Chandra/HETGS data from 2003. We analyzed these three different epochs in a consistent way, looking for absorption features corresponding to highly ionized blueshifted absorption lines from H-like and He-like ions of iron (and nickel), as well as of other elements (O, Ne, Si, and S) in the soft band. We confirm the presence of a persist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 96 publications
(194 reference statements)
2
19
0
Order By: Relevance
“…The third component in the last fit has a velocity of 0.15-0.20 . These values agree well with previous studies (e.g., Reeves et al 2018;Matzeu et al 2017;Boissay-Malaquin et al 2019;Reeves et al 2020). All parameter ranges given here and in the following are 90 % CL.…”
Section: Fitting Spectra Of Pds 456supporting
confidence: 92%
See 1 more Smart Citation
“…The third component in the last fit has a velocity of 0.15-0.20 . These values agree well with previous studies (e.g., Reeves et al 2018;Matzeu et al 2017;Boissay-Malaquin et al 2019;Reeves et al 2020). All parameter ranges given here and in the following are 90 % CL.…”
Section: Fitting Spectra Of Pds 456supporting
confidence: 92%
“…This is the first time that strong evidence for a second outflowing layer has been found in EPIC-pn data alone, which speaks for the sensitivity of the method. Previous evidence for a second layer in PDS 456 was provided by a joined analysis of NuSTAR, XMM-Newton (Reeves et al 2018), and Chandra data (Boissay-Malaquin et al 2019). Their measured outflow velocites of 0.46 ± 0.02 and 0.48 respectively are well within the range of our results (0.41-0.49 ).…”
Section: The Number Of Outflowing Layerssupporting
confidence: 89%
“…15, we also show the momentum boosts and velocities of the ultrafast and molecular outflows of several other AGNs based on published results. Specifically, estimates for PDS 456 are from Boissay-Malaquin et al (2019) and Bischetti et al (2019), estimates for IRAS F11119+3257 are based on Tombesi et al (2015) and Veilleux et al (2017), estimates for APM 08279+5255 are based on Feruglio et al (2017), estimates for IRAS 17020+4544 are from Longinotti et al (2018), estimates for Mrk 231 are from Feruglio et al (2015), and estimates for HS 0810+2554 are based on Chartas et al (2016) and this study. For consistency we have adjusted published results assuming the same conversion factor of α CO = 0.8 M (K km s −1 pc 2 ) −1 for estimating the total molecular gas mass.…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 88%
“…For example, as Chakravorty et al (2012) showed, this can be caused by the strength of the soft excess as well as changes in the temperature of the accretion disc. Among the fairly recent observational papers showing such Scurves are Mehdipour et al (2015), and Mehdipour et al (2016), which shows a very unusual S-curve found for ultra-fast outflow in the quasar PDS 456 (Boissay-Malaquin et al 2019).…”
Section: Update Of the Pion Model In Spexmentioning
confidence: 92%